A NEW SPECIES OF CYMBOPOGON SPRENG. (GRAMINEAE) FROM BURMA - SOENARKO, SOEJATMI (REINWARDTIA, 1975)
An illustrated description of the new species Cymbopogon mandalaiaensis S. Soenarko is presented and it is compared with the closely related species C. nervatus (Hochst.) Chiov. and C. clandestinus (Steud.) Stapf.